2015
DOI: 10.1111/jpet.12119
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Seigniorage

Abstract: There is convincing empirical evidence in cross-section data of a positive correlation between the level of corruption and the rate of inflation. This paper explores whether this correlation can be a consequence of a government exploiting seigniorage to compensate for revenue lost to corruption. We embed corruption within an overlapping generations economy that has money as the only store of value and in which the government optimizes the rate of monetary growth. Three different forms of corruption are modelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(15 reference statements)
2
5
0
Order By: Relevance
“…Our analysis complements and is most closely related to two recent contributions, by Myles and Yousefi (2015) and Ivanyna et al (2015). Myles and Yousefi (2015) explore whether the positive correlation between corruption and inflation, as revealed by cross-section data, can be explained by an optimizing government using seigniorage to compensate for tax revenue lost to corruption. Three forms of corruption are considered: the reduction of effective tax burden, appropriation of tax revenue, and the appropriation of newly produced money.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our analysis complements and is most closely related to two recent contributions, by Myles and Yousefi (2015) and Ivanyna et al (2015). Myles and Yousefi (2015) explore whether the positive correlation between corruption and inflation, as revealed by cross-section data, can be explained by an optimizing government using seigniorage to compensate for tax revenue lost to corruption. Three forms of corruption are considered: the reduction of effective tax burden, appropriation of tax revenue, and the appropriation of newly produced money.…”
Section: Introductionsupporting
confidence: 85%
“…The revenue side of the government's budget constraint comprises seigniorage and tax receipts. The first term on the left-hand-side of equation 6denotes real revenue from money printing or seigniorage (as in Myles and Yousefi, 2015), while the second term gives the actual amount of tax revenue available to the government:…”
Section: Governmentmentioning
confidence: 99%
“…A characterization is provided of when an increase in the size of the public sector will decrease the growth rate. Myles and Yousefi () show that excessive inflation may be a negative side effect of corruption if the government compensates for lost revenue by exploiting seigniorage and increasing the rate of monetary expansion. Ivanyna, Mourmouras, and Rangazas () study the impact on growth of corrupt public officials appropriating funds intended for public investment and demonstrated that this lead to excessively high tax rates.…”
Section: Introductionmentioning
confidence: 99%
“…At the empirical level, we could go further by identifying the channels explaining the nonlinear effect of corruption on inflation on the one hand, and by investigating the impact of corruption on the values of the thresholds of the growth-maximizing seigniorage rate on the other hand. At the theoretical level, future research should also focus on (a) refining the microfoundations of corruption and (b) introducing these microfoundations in other frameworks (in an OLG model, for instance, as Myles & Yousefi, 2015). Second, the introduction of a financial sector affecting the seigniorage revenues retrieved by the government to finance productive public expenditures could be a potential subject for further work.…”
Section: Discussionmentioning
confidence: 99%
“…However, in their model, corruption is not endogenously determined. More recently, Myles and Yousefi (2015) develop a rich and interesting overlapping generation (OLG) model in which money is the only store of value. They model corruption in three different ways and highlight that increasing the seigniorage rate can be a rational strategy for a government which faces a reduction of resources because of corruption.…”
mentioning
confidence: 99%